Analysis of fluorine effects on charge-trap flash memory of W/TiN/Al2O3/Si3N4/SiO2/poly-Si gate stack. (February 2020) - Lee, Tae Yoon; Lee, Seung Hwan; Son, Jun Woo; Lee, Sang Jae; Bong, Jae Hoon; Shin, Eui Joong; Kim, Sung Ho; Hwang, Wan Sik; Moon, Jung Min; Choi, Yang Kyu; Cho, Byung Jin
Highlights: The residual F in the CVD W was diffused into Al2 O3, Si3 N4, SiO2, and the interface at SiO2 /poly-Si after the subsequent annealing process at 900 °C for 1 s. The diffused F increased the SiO2 thickness and altered the charge-trap density in the Al2 O3, Si3 N4, SiO2, and SiO2 /poly-Si interface. The memory window and program/erase retention properties degraded while the charge-transport and endurance characteristics improved with the CVD W memory as compared to the PVD W memory. Abstract: A charge-trap flash (CTF) memory stack of chemical vapor deposition (CVD) tungsten (W) was systematically compared with a physical vapor deposited (PVD) W memory stack. The residual F in the CVD W was diffused into Al2 O3, Si3 N4, SiO2, and the interface at SiO2 /poly-Si after the subsequent annealing process at 900 °C for 1 s. The diffused F increased the SiO2 thickness and altered the charge-trap density in the Al2 O3, Si3 N4, SiO2, and SiO2 /poly-Si interface, and this eventually affected memory performance and reliability. The memory window and program/erase retention properties degraded while the charge-transport and endurance characteristics improved with the CVD W memory as compared to the PVD W memory.